The Legislative Balance between Stability and Sustainability in the Labor Market : A Study of the United Arab Emirates Legislation - Zerara, Aouataf (Journal of Legal Sciences, 2023)
The Emirati Labor Legislation is one of the most effective legislations in its response to the developments and variations of the labor market, an effectiveness attained through emphasizing the necessity of workers’ efficiency reinforcement and through conserving and supporting skilled labor. It is however necessary to maintain balance in labor relations, to achieve equal opportunities for workers, and to ensure their rights, especially the citizens. The United Arab Emirates is actively seeking to support national talent by applying the Emiratization Policy, which is one of the State’s most prioritized concerns. This Policy entails achieving a balance between the labor relations’ stability and meeting the labor market’s requirements which include innovation and performance excellence in order to attain public interest.